The Influence of Auditor Professionalism, Independence, and Ethics on External Audit Quality - Herdiawan, Ricky Andrew; Shonhadji, Nanang; Irwandi, Soni Agus (Lentera Barasaki Publishing House, 2024)
The purpose of this study was to explain the effect of auditor professionalism, independence, and ethics on external audit quality. This research is included in causal research using a quantitative approach, the population of this study are auditors who work at KAP in the city of Surabaya. Sampling used a purposive sampling technique, and the number of samples used was 49 respondents. Data collection was carried out by distributing questionnaires, the questionnaire was the instrument used to obtain respondents' responses. Data were analyzed using Partial Least Square (PLS) with SmartPLS software version 4.0. The results of this research show that professionalism affects external audit quality, independence does not affect audit quality, and auditor ethics affects audit quality.